A Computational Method for Acoustic Interaction with Large Complicated Underwater Structures Based on the Physical Mechanism of Structural Acoustics. (31st December 2022) - Tang, Yongzhuang; Zhou, Qidou; Wang, Xiaowei; Xie, Zhiyong
Abstract : A numerical coupling approach is proposed to fast predict the acoustic radiation from a vibrating large-complicated underwater structure. In this study, the physical mechanism of sound radiation from underwater large target is used for the first time to improve the efficiency and keep the accuracy of the numerical algorithm. Although the traditional coupled finite element method/boundary element method (FEM-BEM) is accurate, it contains a large number of boundary elements and thus requires a long computation time for large-complicated structures. The research on the physical mechanism of structural acoustics shows that when BEM is applied on the near-field artificial boundary at a proper distance away from the wet structural surface, large-size boundary elements are acceptable and the number of boundary elements and computation time are remarkably reduced. Thus, the fluid outside the structure is divided into the interior domain and the exterior domain by the artificial boundary. Then, the numerical method is realized by coupling structural finite element modelling with interior fluid finite element modelling and with exterior fluid boundary element modelling. Compared with the theoretical value, the experimental value and the results of the traditional FEM-BEM, the correctness of the proposed algorithm and its advantage of computational efficiency are verified. The computation time of the proposed method is over 99% shorter than that of FEM-BEM in the calculation example of a large-complicated structure. The proposed method can be further applied to multidomain acoustic and multibody acoustic calculations.